Quality Control Evaluation of SGOT and SGPT Examination Using the Six Sigma Method at PKU Muhammadiyah Bantul Hospital - Ngabalin, Firda; Aji Bagus Widyantara; Isnin Aulia Ulfah Mu’awanah (CV. CENDIKIA JENIUS INDONESIA, 2025)
Quality control is essential to ensure the accuracy and precision of laboratory test results, including SGOT and SGPT as indicators of liver function. This study aims to evaluate the quality control of SGOT and SGPT examinations using the Six Sigma method at PKU Muhammadiyah Bantul Hospital. A descriptive analytic method with a cross-sectional approach was used. The data analyzed consisted of daily control results from July to December 2024 and external quality assurance data. Parameters calculated included mean, standard deviation, coefficient of variation (CV), bias (%d), and sigma values. The results showed that SGOT CV values ranged from 2.40% to 3.19%, and SGPT from 2.24% to 3.51%, both within the acceptable limit of <7%. SGOT bias values ranged from 1.80% to 2.95%, and SGPT from 0.35% to 1.52%, within the acceptable ±10%. Sigma values were 4.2 for SGOT and 4.1 for SGPT, indicating marginal laboratory performance. It is concluded that the accuracy and precision of the tests are acceptable. However, to improve quality, it is recommended that two to three levels of control materials be used in regular quality control implementation.